2015
DOI: 10.31901/24566322.2015/10.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Perception and Experience of Inclusive Education: A Case of a Further Education and Training College in South Africa

Abstract: The aim of this study was to investigate teachers' perceptions of the impact of Continuing Professional Development on promoting quality teaching and learning. This study adopted a mixed method approach using both quantitative and qualitative research designs. Closed-ended self-administered questionnaires and interview schedule were used to collect data. Two hundred teachers were sampled through simple random sampling procedure to complete the questionnaires, while ten teachers participated in face-to-face sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…schools [24]. Since this study was done, many others in the country have revealed similar challenges and very little progress [17,[25][26][27].…”
Section: Plos Onementioning
confidence: 98%
“…schools [24]. Since this study was done, many others in the country have revealed similar challenges and very little progress [17,[25][26][27].…”
Section: Plos Onementioning
confidence: 98%